Boston MFA 38-2-5: A Limestone Fragment with a Hieratic Inscription Presumably from the Reign of Khufu - Jüngling, Johannes (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
This article contains the description, translation, and discussion of Boston MFA 38-2-5, a limestone block found during excavation works at mastaba G(iza) 1203 carried out in 1938 under the supervision of G. A. Reisner. The object bears a dated hieratic inscription in red paint that for the first time is comprehensively translated and analysed. Using up-to-date digital image-enhancement processes, the reading of the date is improved, and certain lexical and grammatical features (the apparent use of a cardinal number instead of an ordinal, names of workforce units, etc.) are discussed. It is argued that the object had been deposited intentionally within the filling of the mastaba during its construction. The article contains a small palaeographic overview of the hieratic signs employed in the inscription.